Overview of Research Progress on White Matter Fiber Bundle Defect Diseases of ADHD, ASD, and OCD - Yang Xilu (BIO Web of Conferences, 2025)
Neurodevelopmental and psychiatric disorders, such as Attention Deficit Hyperactivity Disorder (ADHD), Autism Spectrum Disorder (ASD), and Obsessive Compulsive Disorder (OCD), have received widespread attention due to their profound impact on individual behavior, cognition, and social functioning. The paper reviews the research progress on three neurodevelopmental and psychiatric disorders: ADHD, ASD, and OCD. The article first outlines the social attention of these diseases and their impact on patients’ daily lives, and then explores in detail their clinical features and overlapping symptoms in terms of executive dysfunction, social difficulties, and emotional regulation difficulties. Research has found that although ADHD, ASD, and OCD differ in symptom presentation, they share similarities in neural developmental pathways (the complex series of biological processes that shape the development of the brain and nervous system, which can influence how individuals behave, think, and interact socially), leading to similar challenges in behavioral, cognitive, and social functioning. The paper also discusses the research progress of drug therapy and behavioral therapy as the main treatment methods, emphasizes the importance of early intervention, and proposes the importance of cross disease research (the research of different disorders together to find commonalities that could lead to more targeted and effective treatments for all of them) to promote the development of more precise and effective intervention strategies. Recent advancements in neuroimaging techniques have provided deeper insights into the neural correlates of ADHD, ASD, and OCD, leading to more targeted therapeutic approaches. Additionally, emerging therapies such as transcranial magnetic stimulation (TMS) and neurofeedback are showing promise in managing symptoms and improving functional outcomes in these disorders.